PREDICTION OF THE SURVIVAL OF PATIENTS WITH CLINICAL TUBERCULOSIS AND MYCOBACTERIUM TUBERCULOSIS MULTIPLE DRUG RESISTANCE IN HIV INFECTION - Нина Васильевна Мальцева; Ирина Борисовна Викторова; Ольга Михайловна Казанцева; Светлана Викторовна Архипова; Аркадий Лейбович Ханин; Сергей Николаевич Филимонов (Медицина в Кузбассе)
A search was carried out for prognostic criteria to determine the survival time of patients with tuberculosis in combination with HIV infection. The proposed prognostic coefficient can be used in clinical practice as a criterion for the predicted survival time of patients to increase adherence to treatment and correct treatment tactics for managing patients, which will lead to a decrease in mortality.